Mucosal Administration of Recombinant Baculovirus Displaying Toxoplasma gondii ROP4 Confers Protection Against T. gondii Challenge Infection in Mice - Yoon, Keon-Woong; Chu, Ki-Back; Kang, Hae-Ji; Kim, Min-Ju; Eom, Gi-Deok; Lee, Su-Hwa; Moon, Eun-Kyung; Quan, Fu-Shi (Frontiers in Cellular and Infection Microbiology, 2021)
Pathogens require physical contact with the mucosal surface of the host organism to initiate infection and as such, vaccines eliciting both mucosal and systemic immune responses would be promising. Studies involving the use of recombinant baculoviruses (rBVs) as mucosal vaccines are severely lacking despite their inherently safe nature, especially against pathogens of global importance such as Toxoplasma gondii. Here, we generated rBVs displaying T. gondii rhoptry protein 4 (ROP4) and evaluated their protective efficacy in BALB/c mice following immunization via intranasal (IN) and oral routes. IN immunization with the ROP4-expressing rBVs elicited higher levels of parasite-specific IgA antibody responses compared to oral immunization. Upon challenge infection with a lethal dose of T. gondii ME49, IN immunization elicited significantly higher parasite-specific antibody responses in the mucosal tissues such as intestines, feces, vaginal samples, and brain than oral immunization. Marked increases in IgG and IgA antibody-secreting cell (ASC) responses were observed from intranasally immunized mice. IN immunization elicited significantly enhanced induction of CD4+, CD8+ T cells, and germinal center B (GC B) cell responses from secondary lymphoid organs while limiting the production of the inflammatory cytokines IFN-γ and IL-6 in the brain, all of which contributed to protecting mice against T. gondii lethal challenge infection. Our findings suggest that IN delivery of ROP4 rBVs induced better mucosal and systemic immunity against the lethal T. gondii challenge infection compared to oral immunization.